A control based on a knapsack problem for solar hydrogen production. (27th March 2014) - Roca, L.; Diaz‐Franco, R.; de la Calle, A.; Bonilla, J.; Vidal, A.
Summary: The Hydrosol pilot plant was installed in the small solar power systems solar tower at CIEMAT‐Plataforma Solar de Almería (PSA), Spain, for producing solar hydrogen from water using a ferrite‐based redox technology. It consists of two reactors where hydrogen and oxygen production cycles are alternated for quasi‐continuous hydrogen production. In the first step (water splitting), an exothermic reaction takes place at an operating temperature of 800℃. The second step (thermal reduction) is an endothermic reaction, which requires an operating temperature of 1200℃. Recently, an adaptive control strategy for controlling these operating temperatures in the solar hydrogen reactor has been proposed and implemented, using the number of heliostats focused as the control signal. The algorithm chooses which heliostats have to be focused estimating the concentrated solar power contribution of each heliostat. Then, the heliostats are focused, starting from those which provide lower power. This paper is based on this control strategy, but considering a new algorithm to choose the heliostats. Using the concentrated solar power contributions, a knapsack problem is defined to obtain a local optimal solution, which provides a set of heliostats that minimizes the error between the setpoint and the reactor concentrated solar power. In order to evaluate the performance of this method, simulation and experimental results are shown and discussed. Copyright © 2014 John Wiley & Sons, Ltd.